Use of the Stingray Re-Entry System in Two Complex Cases of Occluded Superficial Femoral Arteries - Erin M. Galbraith; Marc Del Rosario; Khusrow Niazi (Case Reports in Vascular Medicine)
Totally occluded infrainguinal arterial disease presents formidable challenges to endovascular revascularization. A variety of devices have been made available to make the crossing of these lesions more amenable to endovascular techniques. We discuss the novel use of a device that has been developed for crossing occluded coronary arteries, the Stingray Re-Entry System.